Clinicians' attitudes to oncology clinical practice guidelines and the barriers and facilitators to adherence: a mixed methods study protocol. Issue 3 (23rd March 2020) - Bierbaum, Mia; Braithwaite, Jeffrey; Arnolda, Gaston; Delaney, Geoffrey P; Liauw, Winston; Kefford, Richard; Tran, Yvonne; Nic Giolla Easpaig, Bróna; Rapport, Frances
Abstract : Introduction: Clinical practice guidelines (CPGs) are designed to reduce inappropriate clinical variation and improve the quality of care. Barriers to CPGs include a lack of awareness of CPGs, access to them, time pressures and concerns regarding the evidence underpinning CPG development, implementation and dissemination. The objectives of this study are to assess clinicians' attitudes to CPGs for cancer treatment and the perceived barriers to and facilitators of CPG adherence in order to inform the implementation of cancer treatment CPGs. Methods and analysis: A mixed methods study will be conducted using a three-phase, sequential design, with each phase informing the next. In phase 1, a qualitative study using recorded interviews will investigate clinicians' attitudes to CPGs for cancer treatment and perceptions of barriers and facilitators to CPG adherence (n=30); interview transcripts will be analysed thematically. In phase 2, a survey will quantify the frequency of attitudes, barriers and facilitators identified in phase 1, in a broader clinical sample (n=200). In phase 3, a workshop forum will be held to facilitate discussions examining the implications of phase 1 and 2 findings for cancer CPG implementation strategies (n=40) leading to recommendations for improvements to practice. The workshop discussion will be recorded, and the transcript will be analysed thematically. Ethics and dissemination: This study has received ethics approval in New South Wales, Australia (2019/ETH11722, #52019568810127). Study findings will be published in peer-reviewed journals and will form part of a doctoral thesis and be presented at national and international conferences.